Pericardial cyst: An unusual cause of chest pain. Issue 4 (October 2015) - Varvarousis, Dimitrios; Tampakis, Konstantinos; Dremetsikas, Konstantinos; Konstantinedes, Pantelis; Mantas, Ioannis
Abstract Pericardial cysts are uncommon paracardiac lesions, usually located within the right cardiophrenic space. They usually do not cause symptoms and are detected by chance. Chest X-ray, echocardiography, and chest computed tomography or magnetic resonance imaging are useful diagnostic tools. We report a case of a man with symptomatic pericardial cysts of unusual location, review the literature, and discuss the diagnostic approach and treatment options. <Learning objective: Pericardial cysts are uncommon mediastinal lesions, diagnosed safely when suspected by echocardiography and computed tomography or magnetic resonance imaging. An invasive therapeutic approach should be preferred in symptomatic cases.>